Stress Kerja dan Resiliensi Account Representative pada Kantor Pelayanan Pajak di Wilayah Riau dan Kepulauan Riau - Sapti Dwi Iryani; Yanki Hartijasti (Universitas Airlangga, 2018)
This study focused on job stress and employee resilience of Account Representative at Tax Offices in Riau and Riau Islands region. This research used qualitative content analysis method. Respondents that were involved in this study were 154 Account Representative. Based on data analysis, there were two major themes, namely job stress factor and resilience factor. The theme of job stress consisted of two categories, namely factors causing stress due to work and factor causesing stress beside of work. The theme of resilience factors consisted of internal protective factor and external protective factor. The calculation of qualitative content analysis found that the highest cause of stress at work was due to the intrinsic to job subcategory while the biggest cause of stress from outside was due to extra-organizational factors. The factor of religiousity and spirituality became the highest internal protective factor while the support factor became the highest external protective factor.